The Role of Visual Content and Influencers in Digital Marketing - Alfreldo, Farhan (Economic and Business Horizon, 2024)
Digital marketing through social media, especially Instagram, has experienced rapid development in recent years. This study aims to analyze how digital marketing strategies can increase consumer engagement and expand market reach. Key elements in digital marketing, such as engaging visual content, influencer marketing, and paid advertising, are critical factors in the success of marketing campaigns on social media. The research method used is a qualitative approach with a descriptive analysis of digital marketing strategies implemented through social media, especially Instagram. The results show that companies that make optimal use of social media can increase interaction with customers, strengthen brand identity, and increase sales conversions. In addition, innovations in content creation and the use of technologies such as artificial intelligence and data analysis also support the effectiveness of digital marketing. Therefore, investing in digital marketing is a very important step for companies that want to stay ahead of the digital age.